Portfolio Substitutability, Regulations, and Monetary Policy - Silber, William L. (Quarterly Journal of Economics, 1969)
I. Introduction, 197. — II. Substitutability: theoretical arguments, 198. — III. Empirical tests: general approach, 200. — IV. Conclusions regarding regulations and monetary policy, 213. — Appendix, 213.